Multiple tuning curve based wideband RC VCO design / Muhammad Awais - Muhammad, Awais (2017)
Voltage controlled Oscillator (VCO) is a key element in defining overall system specification. It is widely used in communication equipment as an essential part of frequency synthesizers and phase-locked loops (PLL). In achieving high tuning range performance an oscillator pays its penalty in degraded phase noise output. Resorting into a LC based VCO at high frequency which exhibit superior phase noise performance foresees large active area consumption with a proportional increase in the cost. The evolution of deep-submicron CMOS technology mandates the need of low power solution with a proportional headroom limitation. In view of the highlighted challenges, this work proposes a RC based Voltage Controlled Oscillator (RC-VCO) with programmable tuning curves to achieve a wideband frequency operation. Fabricated and characterized in 130 nm standard CMOS platform, the VCO switches between the tuning curves with a programmable current injection. The VCO exhibit a frequency operation between 2.05 to 4.19 GHz, resulting in a wideband tuning range of 68.5%. The proposed architecture consumes a maximum dc current of 8.8mA measured at the highest frequency of operation. The design also observes a phase noise of -99.3 dBc/Hz at an offset of 1MHz with a carrier of 4.19GHz. The proposed RC-VCO achieves a Figure of Merit of -161.4 dBc/Hz (FOM) and -178.1 dBc/Hz (FOMT), respectively. The summary of performance favours the architecture in the integration of a wideband frequency synthesizer.